Relate North 10 - Possible futures : exhibition catalogue - O´Grady, Aubyn; Jokela, Timo; fi=Taiteiden tiedekunta|en=Faculty of Art and Design| (fi=Lapin yliopisto|en=University of Lapland|, 2023)
Relate North Possible Futures is a collaboration between the University of the Arctic’s Arctic Sustainable Arts and Design Thematic Network (ASAD), the Yukon School of Visual Arts (Yukon University), and the University of Lapland. The ASAD Network aims to identify and share innovative practices in learning, teaching, research and knowledge exchange in art, design and visual culture education. The network promotes cooperation and collaboration between academic institutions and communities to work towards a shared understanding of critical issues relevant to people living in the North. The tenth annual Relate North Virtual Exhibition includes projects from across the circumpolar Arctic that engage with this year’s network theme: Possible Futures. Arctic communities are at the forefront of imagining alternative futures in a rapidly changing present. Across the ASAD Network, there are many examples of initiatives actively working towards creating alternatives, from land-based educational projects to the inclusion of Indigenous language and cultural revitalization programming to collaborations between community-led arts-based researchers and scientists. The virtual exhibition launched concurrently with the Relate North Virtual Symposium (28-29 January, 2023) broadcast from the Ayamdigut campus of Yukon University, in Whitehorse, Yukon, on the traditional territories of the Ta’an Kwäch’än Council and the Kwanlin Dün First Nation. Every year the Relate North Symposium & Exhibition attracts leading scholars and artists from around the circumpolar North to present research and debate issues of concern to arctic and subarctic regions through the lens of art and design. The tenth annual Relate North symposium was a platform to support relations between network partners to mobilize and share examples of what we know “works” at each of our specific sites. Participants discussed strategies for how to ethically and intentionally evolve our institutions, projects, and practices to align with, support, and enact the many ...